Characterization of phospholipids in coconut milk during fermentation to obtain virgin coconut oil - HENSON, DEJARME (Archīum Ateneo, 2012)
Nuclear magnetic resonance (31P NMR) and UV-visible spectroscopy. Using 31P NMR, it was shown that during fermentation of coconut milk prepared under controlled laboratory conditions, the phosphorus signals in coconut milk disappeared in parallel with an